DINAMIKA GERAKAN ISLAM LIBERAL DI INDONESIA - Agus Riyanto (SPEKTRUM, 2008)
Abstract The debate of Islamic Thought in Indonesia after new order is dominated by conflict between radical Islamic and liberal thought. Modernization in Islamic World have driven the modernization and liberation process in Islamic Thought especially it have risen liberal Islamic with affirmative to West Ideas as democracy, pluralism, and humanism. This article will explain about the dynamic of Liberal Movement in Indonesia.